A review on microplastics and nanoplastics in the environment: Their occurrence, exposure routes, toxic studies, and potential effects on human health. (August 2022) - Sangkham, Sarawut; Faikhaw, Orasai; Munkong, Narongsuk; Sakunkoo, Pornpun; Arunlertaree, Chumlong; Chavali, Murthy; Mousazadeh, Milad; Tiwari, Ananda
Abstract: Microplastics (MPs) and nanoplastics (NPs) are emerging environmental pollutants, having a major ecotoxicological concern to humans and many other biotas, especially aquatic animals. The physical and chemical compositions of MPs majorly determine their ecotoxicological risks. However, comprehensive knowledge about the exposure routes and toxic effects of MPs/NPs on animals and human health is not fully known. Here this review focuses on the potential exposure routes, human health impacts, and toxicity response of MPs/NPs on human health, through reviewing the literature on studies conducted in different in vitro and in vivo experiments on organisms, human cells, and the human experimental exposure models. The current literature review has highlighted ingestion, inhalation, and dermal contacts as major exposure routes of MPs/NPs. Further, oxidative stress, cytotoxicity, DNA damage, inflammation, immune response, neurotoxicity, metabolic disruption, and ultimately affecting digestive systems, immunology, respiratory systems, reproductive systems, and nervous systems, as serious health consequences. Graphical abstract: Unlabelled Image Highlights: Occurrences, sources, and exposure routes of MPs are reviewed. Experimental and modeling case studies about the fate and transport of MPs/NPs are summarized. Probable human health consequences of MPs/NPs are reviewed. Existing knowledge gaps and future research directions are discussed.